Survey on the Production of Traditional Bioenergy in the Democratic Republic of the Congo: The Case Study of Kwilu Province - Masens Da-Musa Y.B.; Koto-te-Nyiwa Ngbolua; Briki C. Kakesa; Muhammad Ridwan (Britain International of Exact Sciences (BIoEx) Journal, 2021)
The present research has been carried out in three different groupings, namely Mudikwiti, Tanganga and Nkata in Kwilu province, in the Democratic Republic of the Congo. 165 coalmen from eighteen villages have been considered as the sample used in this work. They are selected from all social strata, and their ages vary from 18 to 30 years old and from 44 to 56 years old. They have made 21,899 ovens, among which there were 12, 287 ovens of small dimensions, that is, 1 m x 6 m x 3 m, and 9,612 ovens of big dimensions: 6 m x 20 m x 3 m. They have cut 196,694 trees of different species to fill in the two kinds of ovens, say 99,984 trees for filling in small ovens and 96,710 trees to fill in big ovens. On the whole, they have produced 852,708 sacks of charcoal per year. The Nkata grouping, with its 11 villages, has produced 129,600 sacks of 45 kilograms, divided as follows: 14,400 sacks from the small dimension ovens and 115, 200 sacks from the big dimension ovens.